2020
DOI: 10.1200/jop.19.00643
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Infusion Clinic Wait Times Using Quality Improvement

Abstract: PURPOSE: Long wait times are a common occurrence for chemotherapy infusion patients and are a source of decreased patient satisfaction. Our facility sought to decrease outpatient infusion clinic wait times by 20% using the Model for Improvement, quality improvement tools, and Plan-Do-Study-Act cycles. METHODS: A multidisciplinary team was formed to address clinic wait times. Patient interviews, time studies, process mapping, brainstorming sessions, affinity diagrams, fishbone diagrams, and surveys were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 6 publications
2
10
0
Order By: Relevance
“…The findings of a national survey of hospitals and their use of quality improvement studies offer potential to improve the care process, as measured by standard indicators of hospital performance [ 44 ]. Such approaches are receiving recognition as an important component of quality cancer care along the care continuum, including survivorship planning [ 45 ]; reducing infusion wait time [ 46 ]; participation in interdisciplinary conferences [ 47 ]; and improving tobacco cessation in a clinic setting [ 48 ].…”
Section: Practice Implications: the Role Of Managementmentioning
confidence: 99%
“…The findings of a national survey of hospitals and their use of quality improvement studies offer potential to improve the care process, as measured by standard indicators of hospital performance [ 44 ]. Such approaches are receiving recognition as an important component of quality cancer care along the care continuum, including survivorship planning [ 45 ]; reducing infusion wait time [ 46 ]; participation in interdisciplinary conferences [ 47 ]; and improving tobacco cessation in a clinic setting [ 48 ].…”
Section: Practice Implications: the Role Of Managementmentioning
confidence: 99%
“…Studies have also shown that quality improvement (QI) initiatives aimed at reducing wait times at outpatient cancer infusion centers have also contributed to patient satisfaction 18,19. These studies serve as an example of how targeted QI initiatives can help improve the care provided in outpatient infusion settings.…”
Section: Introductionmentioning
confidence: 99%
“…Infusion centres serve patients with neurological diseases and other conditions (e.g., oncological and rheumatological) with finite resources, putting them at risk of being overburdened. Literature indicates that infusion centres commonly experience long waiting times: the time from treatment decision to administration, and waiting times from patient arrival until start of infusion [ 9 ]. This can lead to suboptimal clinical outcomes and patient dissatisfaction [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Literature indicates that infusion centres commonly experience long waiting times: the time from treatment decision to administration, and waiting times from patient arrival until start of infusion [ 9 ]. This can lead to suboptimal clinical outcomes and patient dissatisfaction [ 9 , 10 ]. Delays in treatment administration warrant more effective short-term resource utilisation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation